2012
DOI: 10.5535/arm.2012.36.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Supraspinatus Muscle Thickness Measurement by Ultrasonography

Abstract: ObjectiveTo assess the intrarater and interrater reliability of the supraspinatus thickness measured by ultrasonography (US) in normal subjects and to identify the relationship between the supraspinatus thickness measured by US and cross sectional area (CSA) of the supraspinatus muscle by magnetic resonance imaging (MRI) in hemiplegic patients.MethodWe examined 20 shoulders of normal subjects and 10 shoulders of hemiplegic patients. In normal subjects, one examiner measured the supraspinatus thickness twice by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…There is a paucity of studies that investigated the reliability of morphological measurements of supraspinatus muscle (Katayose and Magee, 2001;Yi et al, 2012), but none of them included physical therapists as operator. The aim of this study was to establish the reliability of morphometric measurements made by two physical therapists in a same day testeretest study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of studies that investigated the reliability of morphological measurements of supraspinatus muscle (Katayose and Magee, 2001;Yi et al, 2012), but none of them included physical therapists as operator. The aim of this study was to establish the reliability of morphometric measurements made by two physical therapists in a same day testeretest study.…”
Section: Discussionmentioning
confidence: 99%
“…Juul-Kristensen et al (2000) reported a mean thickness of 20.1 mm at the supraspinatus midpoint. A recent study by Yi et al (2012) measured the supraspinatus thickness and determined means of 17.2 AE 2.1 mm for rater 1 and 17.4 AE 2.2 mm for rater 2. The measurement point was in the distal part of the muscle, near the acromion.…”
Section: Figure 5 Bland and Altman Plot Showing Intrarater Reliabilitmentioning
confidence: 99%
“…Therefore, it is important to know whether MT is related to anatomical muscle CSA and MV in an individual muscle of the extremity and trunk. Previously, the linear relationship between MT and muscle CSA or MV has been observed in the quadriceps (Sipila & Suominen, ; Abe et al ., ), adductor (Ogawa et al ., ), triceps surae (Miyatani et al ., ), tibialis anterior (Martinson & Stokes, ), biceps brachii (Akagi et al ., ), triceps brachii (Miyatani et al ., ), pectoralis major (Yasuda et al ., ), supraspinatus (Yi et al ., ) and psoas major (Takai et al ., ) muscles. Other major muscle groups in the body such as hamstring, however, have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also reported with the psoas major muscle in that CSA measured by MRI is highly (r ¼ 0.95, p < 0.05, n ¼ 11) correlated to MT of the psoas major measured by ultrasound. 30 In addition, Yi et al 28 found a high correlation (r ¼ 0.76, p ¼ 0.01, n ¼ 10) between ultrasound measured supraspinatus MT and MRImeasured supraspinatus muscle CSA in hemiplegic patients. Although there are a limited number of studies, the results are similar to MT of the upper extremity in that MT in the trunk may reflect muscle CSA and MV of the individual trunk muscles.…”
Section: Association Between Mt and Muscle Csa Or MVmentioning
confidence: 99%